A case of fatal envenomation by a captive puff adder (Bitis arietans) in Malaysia. (1st March 2023) - Husain, Zulfahimi; Wicaksono, Aji Caesar; Renault, Asyhok; Md Zhahir, Siti Sarah; Ismail, Ahmad Khaldun
Abstract: The Puff Adder ( Bitis arietans ) is a viper native to Africa and the Middle East. Envenomation by this species often requires the administration of appropriate antivenom in order to achieve a favorable outcome. A patient was bitten in both hands by a captive B. arietans presented to a teaching hospital in Malaysia. The patient developed painful progressive swelling on both limbs that extended to the chest, hypotension, hypokalemia with worsening anemia, thrombocytopenia, coagulopathy, and severe metabolic acidosis. The patient was managed supportively while waiting for the appropriate antivenom, Antivipmyn-Africa, from the Singapore Zoo. The patient developed cardiorespiratory arrest twice and did not recover from the second. The patient was pronounced dead 23 hours post-incident. The local unavailability of the appropriate antivenom may be the most important factor that contributed to the patient's death. There is also a need to amend the Malaysian Wildlife Act in order to prevent such cases from recurring. Graphical abstract: Image 1 Highlights: This is the first documented incident of Bitis arietans bite envenomation in Malaysia. Close observation of envenomation progression is essential. Clinical features included: edema, hypotension, hypokalemia, anemia, thrombocytopenia, coagulopathy, and metabolic acidosis. The outcome may have been influenced by the unavailability of specific antivenom for captive exotic venomous snakes. The inadequacy of the current Malaysian wildlife act is reflected in this incident.